Pengaruh Model Pembelajaran Selft Regulated Learning terhadap Kemampuan Berpikir Kreatif Siswa Kelas 3 Kok SAI Anusorn School Thailand - Sofiyah, Nurul; Wanda, Karina; Perwira, Suci (Tarbiatuna: Journal of Islamic Education Studies, 2024)
It is hoped that imaginative reasoning abilities can develop humans and overcome problems experienced in everyday life. Looking at the results of the investigation of Grade 3 KOK SAI Anusorn School Thailand students, the imaginative abilities of students in Thailand are generally very perfect. Low imaginative reasoning. Student capacity can be realized through a learning model where students are able to work based on students' innovative thinking. Self-Control Learning Model A learning model where students are given the opportunity so that some of the students' low innovative reasoning can be improved to face their own learning. This exam is expected to determine the impact of the Oneself Directed Picking learning model on the innovative reasoning skills of Class 3 students at KOK SAI Anusorn School Thailand. The number of grade 3 students at KOK SAI Anusorn School Thailand is increasing rapidly. The example is taken using a group irregular checking strategy to get class 3. The technique used is the test strategy and. The test results show that there is an influence of the Oneself Controlled Picking learning model on students' innovative reasoning abilities.